Interação universidade-empresa em biotecnologia: estudos de caso em laboratórios de pesquisa universitários estadunidenses e brasileiros - Karla Rocha Liboreiro (2020)
The aim of this thesis is to analyze how the factors associated with research infrastructure, qualification of the laboratory teams, and local incentives influence the university-industry interaction (UII) in the area of biotechnology. The National Innovation Systems approach is used to carry out two parallel case studies in different national contexts: the United States of America (University of California Berkeley) and Brazil (Federal University of Minas Gerais). Four university biotechnology research laboratories were selected, a technological area directly related to the advancement of scientific knowledge. We employed three methodological strategies: the application of two questionnaires, previously validated - BR Survey and IPEA-Infra; ten interviews with key respondents from each laboratory; and documentary research on the websites of governmental intellectual property agencies, universities, and laboratories. The results revealed characteristics of the knowledge transfer channels via UII, identified mainly as patent licensing, publications, and spin-off generation, the latter being the most significant. A characteristic of the research laboratories investigated is the existence of historical biological samples, which contributed to the interest of companies in testing kits for diagnosing diseases, thus constituting a channel for knowledge transfer. Among the incentives to the UII with a positive impact, in the American case, financial resources granted by the government to carry out collaborative research (university-company) and the formal and consolidated support structure for the UII stand out. In the Brazilian case, there was low participation in UII by the private industrial sector, largely due to the lack of interest in establishing partnerships with educational institutions. The study revealed a new institutional arrangement format differentiated from the Brazilian academic spin-offs - with a bilateral hybrid function of networks connecting with the industrial sector, which favors the increase in the absorptive capacity of companies and, above all, allows laboratories to disclose their technologies and research results. Among the contributions of this research, we mention the proposal of an analytical framework for UII, integrating data from research laboratories, factors preceding the university-industry interaction, and possible results types of this interaction. This milestone presents new perspectives for the elaboration of national and local policies to stimulate UII, and in particular, the generation of academic spin-offs. The research contributed to expand the empirical literature by using parallel case studies on the subject and to reinforce the importance of institutional practices in universities for the promotion and monitoring of university-industry interactions.